O turismo e a aquisição da produção rural familiar e da pesca pelos serviços de alimentação e acomodação em São Miguel do Gostoso (RN) - Gonçalves, Anna Laurytha Carlos (2018)
The present study investigated the relationship of tourism with the acquisition of the rural family and fisheries production by food service and accommodation in São Miguel do Gostoso (RN), since tourism while socio-spatial phenomenon can contribute improvements to the municipality and to the people who live there. That said, the perspective of Amartya Sen (2010), which addresses the development as freedom, Kiyota and Gomes (1999); Belik et al. (2002) and Ramalho (2016), to support the debate on relations of the local economy. In this scenario, as participants of research the tourist trade and the farmer. To reach such audience participant, were considered some of the criterion: a) the tourist trade there should be at least a year and provide at least one meal in your establishment; and b) farmers were study from the endorsements made by the tourist trade identifying them as food vendors acquired for your establishment. The scope of the study is exploratory and descriptive, Qualitative-quantitative approach. At first, it mentions the difficulty of obtaining information about the existence of establishments of accommodation and food due, too, to the high frequency of companies that come and go from this sector. Skirted-if such a situation using several existing information about the enterprises concerned, to reach the business objective. The data were collected with the enterprises and farmers who fell in the search criteria. The answers obtained in data collection were used to assemble the census of the tourist trade relevant to the following analyses, the interviews were carried out with those who recognized acquire rural food production directly to the farmer. In sequence, interviewed farmers selling your rural family production in free marketing fair in São Miguel do Gostoso (RN). All the information of the census were entered in to Google Forms, to assist in the analysis and interpretation of data. The interviews already had their audio transcribed according to guidelines the Ramilo and Freitas (2001), and subsequently, the analysis of the content. It can be said that the main findings on the relationship of the acquisition of food grade are: 1) the accommodation service is one that stands out with the acquisition of food directly to family agriculture; 2) the food service for the purchase directly to other markets, and the local market little using the acquisition of food directly to family agriculture; 3) the tourist trade that has consumption are those who seek to acquire the food directly to family agriculture; 4) the acquisition of food directly from local market is bigger than the acquisition of fair market, family farming and organic fair, respectively; and 5) for establishment of the tourist trade that has no link with the acquisition of food directly to family agriculture.